Políticas linguísticas nos projetos políticos pedagógicos das escolas indígenas Karajá - Gomes, Fernanda Cardoso da Cunha (2016)
With this study, I have the main objective to present the language policy vitality built by Karajá students of the course of Specialization in Intercultural Education and Transdisciplinary: pedagogical management, Federal University of Goiás, which make up the pedagogical political projects of the schools of Hawalò, Itxala and Btoiry. In it I discuss, first, the historical and social context of the Karajá people, in order to understand the complex universe, plural and specific experienced by these people in Brazil. The second chapter of this study has the objective to discourse about public policies on Indigenous Education in Brazil, from the Indian Protection Service, founded in 1910, until term of the 1988 Federal Constitution. In the third chapter, we discuss the concepts of interculturalism and transdisciplinary in the process for specific differentiated indigenous education in order to understand how teachers and indigenous students experience these principles in the course of specialization, taking prospects to bring possibilities to recognize and appreciate other cultural and educational systems that will beyond the cultural hierarchy, language and education in the construction of educational policy projects of their schools. And finally, in the fourth chapter, we present the sociolinguistics situation of the mentioned villages, detailing the language uses realities of the Karajá people in their social spheres of linguistic and cultural production in these communities. It is important noting that the sociolinguistic study is authored by Karajá teachers and is the basis of creation of language policies that make up the pedagogical political projects of schools in question. For the presentation and study of these language policies, I support this research in Toral (1992), Pimentel da Silva (2001a, 2004), Walsh (2009), the pedagogical political projects the schools of the villages of Hawalò, Itxala and Btoiry (2014) and interviews with students graduating teachers of the specialization course. I intend, with this work, collaborate with research on language policies vitality of indigenous Brazilian languages, but also and especially with the training of teachers Karajá, providing them grants for study and reflection of contextualized methodologies and intercultural bilingual education to consider the uses and functions of their languages and other, such as the Portuguese language, both inside and outside the school in the process of oral communication and writing.